Trypanosoma cruzi Coaxes Cardiac Fibroblasts into Preventing Cardiomyocyte Death by Activating Nerve Growth Factor Receptor TrkA - Aridgides, Daniel (Public Library of Science, 2013)
RATIONALE: Cardiomyocytes express neurotrophin receptor TrkA that promotes survival following nerve growth factor (NGF) ligation. Whether TrkA also resides in cardiac fibroblasts (CFs) and underlies cardioprotection is unknown. OBJECTIVE: To test whether CFs express TrkA that conveys paracrine signals to neighbor cardiomyocytes using, as probe, the Chagas disease parasite Trypanosoma cruzi, which expresses a TrkA-binding neurotrophin mimetic, named PDNF. T cruzi targets the heart, causing chronic debilitating cardiomyopathy in ∼30% patients. METHODS AND RESULTS: Basal levels of TrkA and TrkC in primary CFs are comparable to those in cardiomyocytes. However, in the myocardium, TrkA expression is significantly lower in fibroblasts than myocytes, and vice versa for TrkC. Yet T cruzi recognition of TrkA on fibroblasts, preferentially over cardiomyocytes, triggers a sharp and sustained increase in NGF, including in the heart of infected mice or of mice administered PDNF intravenously, as early as 3-h post-administration. Further, NGF-containing T cruzi- or PDNF-induced fibroblast-conditioned medium averts cardiomyocyte damage by H(2)O(2), in agreement with the previously recognized cardioprotective role of NGF. CONCLUSIONS: TrkA residing in CFs induces an exuberant NGF production in response to T cruzi infection, enabling, in a paracrine fashion, myocytes to resist oxidative stress, a leading Chagas cardiomyopathy trigger. Thus, PDNF-TrkA interaction on CFs may be a mechanism orchestrated by T cruzi to protect its heart habitat, in concert with the long-term (decades) asymptomatic heart parasitism that characterizes Chagas disease. Moreover, as a potent booster of cardioprotective NGF in vivo, PDNF may offer a novel therapeutic opportunity against cardiomyopathies.